Enhanced Yield of Pepper Plants Promoted by Soil Application of Volatiles From Cell-Free Fungal Culture Filtrates Is Associated With Activation of the Beneficial Soil Microbiota - Baroja-Fernández, Edurne; Almagro, Goizeder; Sánchez-López, Ángela María; Bahaji, Abdellatif; Gámez-Arcas, Samuel; De Diego, Nuria; Dolezal, Karel; Muñoz, Francisco José; Climent Sanz, Eric; Pozueta-Romero, Javier (Frontiers in Plant Science, 2021)
Plants communicate with microorganisms by exchanging chemical signals throughout the phytosphere. Such interactions are important not only for plant productivity and fitness, but also for terrestrial ecosystem functioning. It is known that beneficial microorganisms emit diffusible substances including volatile organic compounds (VOCs) that promote growth. Consistently, soil application of cell-free culture filtrates (CF) of beneficial soil and plant-associated microorganisms enhances plant growth and yield. However, how this treatment acts in plants and whether it alters the resident soil microbiota, are largely unknown. In this work we characterized the responses of pepper (Capsicum annuum L.) plants cultured under both greenhouse and open field conditions and of soil microbiota to soil application of CFs of beneficial and phytopathogenic fungi. To evaluate the contribution of VOCs occurring in the CFs to these responses, we characterized the responses of plants and of soil microbiota to application of distillates (DE) of the fungal CFs. CFs and their respective DEs contained the same potentially biogenic VOCs, and application of these extracts enhanced root growth and fruit yield, and altered the nutritional characteristics of fruits. High-throughput amplicon sequencing of bacterial 16S and fungal ITS rRNA genes of the soil microbiota revealed that the CF and DE treatments altered the microbial community compositions, and led to strong enrichment of the populations of the same beneficial bacterial and fungal taxa. Our findings show that CFs of both beneficial and phytopathogenic fungi can be used as biostimulants, and provide evidence that VOCs occurring in the fungal CFs act as mediators of the plants’ responses to soil application of fungal CFs through stimulation of the beneficial soil microbiota.